How to look at stained glass : a guide to the church windows of England - Brocket, Jane (I.B. Tauris, 2018)
The magical qualities of stained glass have an enduring appeal, but church windows tend to be ignored as a form of creative and artistic expression. How to Look at Stained Glass is a fresh, unstuffy guide, which explores the medium by themes, patterns, designs, and effects. Using an A-Z format to reveal a multitude of fascinating details - all the way from apples to zig-zags - it makes looking at gloriously colourful, artistically important windows entertaining and rewarding. This layman's guide requires no previous historical, artistic or religious knowledge and the A-Z miscellany is in keeping with the pot-luck mix of windows to be found in most churches. It covers all the major periods and styles from medieval to modern, Victorian to post-war, eighteenth century to Arts and Crafts, figurative to abstract, and examines the fascinating and evolving iconography of stained glass